Queer Malay identity formation - Collin, Jerome (Routledge, 2013)
This article examines identity formation among queer Malays in the works of two Malaysian Malay writers, Karim Raslan and Dina Zaman. It begins with a brief discussion of Malay identity politics, followed by an analysis of identity creation processes among queer Malays who are featured in Karim and Dina’s works. The analysis focuses on the various markers and strategies queer Malays in the said works used to construct their identity, as well as the tensions and conflicts they experience in creating and expressing a Malay Muslim identity marked by queerness. The findings here posit that non-normative sexualities, in addition to Malay culture and religion, are key to queer Malays’ notions of being Malay in present-day Malaysia.